1997
DOI: 10.1021/jo970570q
|View full text |Cite
|
Sign up to set email alerts
|

Use of Conjugated Dienones in Cyclialkylations:  Total Syntheses of Arucadiol, 1,2-Didehydromiltirone, (±)-Hinokione, (±)-Nimbidiol, Sageone, and Miltirone

Abstract: Functionalized hydrophenanthrenes can be prepared using a cyclialkylation-based strategy. These annulations are highly dependent on the directing effects of the arene substitutents and on conformational considerations. The utility of this methodology was featured in the syntheses of six diterpenoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…9 Furthermore, the additional application could synthesize miltirone by the reduction of the ketone group in 6, 5 de-methylation of the methyl ether and the subsequent Dess-Martin oxidation. 4 In conclusion, we have developed a short synthesis route to versatile intermediate 6 via Suzuki coupling as a key reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Furthermore, the additional application could synthesize miltirone by the reduction of the ketone group in 6, 5 de-methylation of the methyl ether and the subsequent Dess-Martin oxidation. 4 In conclusion, we have developed a short synthesis route to versatile intermediate 6 via Suzuki coupling as a key reaction.…”
Section: Resultsmentioning
confidence: 99%
“…2 Due to their important activities, research has focused on the total syntheses of these compounds. [3][4][5] In our endeavor to modify bioactive abietane diterpenes for medical purposes, we found that compound 6 was a key intermediate to accomplish total synthesis of xanthoperyl methyl ether 2 and pisiferic acid 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Allyl bromobenzene 4 was prepared according to procedures described earlier. 13,14 Dimethyl 2 allylphenylboronate (5). A solution of 4 (10.23 g, 41 mmol) in THF (50 mL) was added to magnesium chips (1.1 g, 45 mmol) activated with 1,2 dibromoethane in THF (20 mL).…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] On the basis of these unsuccessful preliminary results, we decided to first establish the suitable experimental conditions for the protection of the ketone moiety of the ketophosphonate 1a using ethylene glycol or ethane-1,2-dithiol commonly used for this purpose. At the same time, we envisionned to explore the reaction of other N-nucleophiles including hydrazines, tosylhydrazines, [16][17][18][19][20][21][22][23][24] and hydroxylamine 25-31-32-33 on the enone moiety. Hence, we wish to report in this paper our results on the chemoselective reaction of these Sand N-nucleophiles on a series of γ-keto allyl phosphonates.…”
Section: Introductionmentioning
confidence: 99%